The Influence of Digital Literacy, Creativity, and Tolerance for Ambiguity with Generation Z's Entrepreneurial Attitude with Growth Mindset as a Mediating Variable - Pranata, Agung; Suhardi, Suhardi; Afrizal, Afrizal; Sugianto, Efendi (Economic: Journal Economic and Business, 2025)
This study explores the influence of digital literacy, creativity, and tolerance for ambiguity on the entrepreneurial attitude of Generation Z, with growth mindset as a mediating variable. Generation Z, as digital natives, possess extensive access to technology, yet entrepreneurial attitudes among them remain uneven. Drawing from socio-cognitive and entrepreneurial mindset theories, this research employs a quantitative approach using a structured survey and partial least squares structural equation modelling (PLS-SEM) to analyze responses from 137 Gen Z participants. The findings reveal that digital literacy significantly affects growth mindset, which in turn strongly influences entrepreneurial attitude. However, digital literacy, creativity, and ambiguity tolerance do not show direct significant effects on entrepreneurial attitude. Only the growth mindset mediates the relationship between digital literacy and entrepreneurial attitude significantly, highlighting its pivotal role. These insights underline the importance of fostering a growth-oriented learning environment and strengthening digital competence to encourage entrepreneurial behavior. The study contributes theoretically by expanding the mediating role of growth mindset and offers practical implications for entrepreneurship education tailored to Generation Z in the digital age.